Optimization of an oil recovery process from oily sludge using a combined technique of froth flotation and centrifugal treatment. (10th May 2023) - Li, Wenying; Ma, Yanfei; Feng, Xuedong; Alheshibri, Muidh; Bu, Xiangning; Ma, Guangxi; Ni, Mengqian; Li, Qiuhong; Liu, Aiju; Niu, Xiaoyin
Abstract: Petroleum refining usually produces hazardous sludge accompanied by hydrocarbons and heavy metals. Accordingly, this work evaluates the performance of a chemical agent-free approach using froth flotation and centrifugation to enhance the separation of oil and solid materials at normal temperatures. Here, the effects of a flotation reagent, temperature, time, ratio of liquid to oil sludge, and impeller speed were analyzed to reduce the oil content of residue. Furthermore, a centrifugal treatment was used to reduce the solid content of the oil phase recovered from the flotation process. The properties of the solids in the oil sludge, oil phase, and residue were assessed by a laser particle size analyzer, X-ray fluorescent spectrometer, and X-ray diffraction analyzer. The results showed that the oil recovery and the oil content of residue were 93.7% and 3.1%, respectively, at a flotation time of 25 min, an impeller speed of 1580r/min, and an OS/flotation liquid ratio of 1:12, with tap water as the flotation liquid under 33 °C. Fine particles (<45 μm) comprising secondary minerals entered the oil phase. Subsequently, the solid content of the oil phase collected from the flotation system could be reduced to 0.8% with a centrifugal treatment at 5 min, speed of 4, 000r/min, and oil/water ratio of 1:4 under 80 °C. The aqueous phase from the flotation and centrifugation processes can be reused in the flotation process. Highlights: Combining flotation and centrifugation achieved 93.7% oil recovery from oil sludge. The solid content of the recovered oil was reduced to 0.8%. The classical first-order model described better the flotation process of oil sludge. The wastewater is recycled in the flotation process without discharge.